2011
DOI: 10.1128/aem.01213-10
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes of Freshwater Ammonia-Oxidizing Archaeal Assemblages and Nitrogen Species in Oligotrophic Alpine Lakes

Abstract: The annual changes in the composition and abundance of ammonia-oxidizing archaea (AOA) were analyzed monthly in surface waters of three high mountain lakes within the Limnological Observatory of the Pyrenees (LOOP; northeast Spain) using both 16S rRNA and functional (ammonia monooxygenase gene, amoA) gene sequencing as well as quantitative PCR amplification. The set of biological data was related to changes in nitrogen species and to other relevant environmental variables. The whole archaeal assemblage was dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 70 publications
8
107
3
2
Order By: Relevance
“…S1). Most of the sequences matched the soil/fresh-1 group (cluster A, in Auguet et al, 2011). In turn, OTU À 12 (very abundant at the bottom of the lake in winter-spring, and responsible for splitting this sample from the remaining April samples, Figure 6a) fell into the fresh/low-salinity group (cluster C), which has 95% identity with the amoA sequence of N. limnia.…”
Section: July20mmentioning
confidence: 95%
See 3 more Smart Citations
“…S1). Most of the sequences matched the soil/fresh-1 group (cluster A, in Auguet et al, 2011). In turn, OTU À 12 (very abundant at the bottom of the lake in winter-spring, and responsible for splitting this sample from the remaining April samples, Figure 6a) fell into the fresh/low-salinity group (cluster C), which has 95% identity with the amoA sequence of N. limnia.…”
Section: July20mmentioning
confidence: 95%
“…Spatio-temporal changes in the distribution of planktonic freshwater AOA are, however, poorly documented (Pouliot et al, 2009;Llirós et al, 2010;Auguet et al, 2011) in contrast to what is known in the marine realm. The characteristic AOA abundance peak observed in the oxygen-minimum zone and dimly lit oceanic waters are often associated to maxima in nitrite concentrations, suggesting active ammonia oxidation in these areas.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the last decade, several studies have shown the broad distribution and abundance of Archaea in aquatic ecosystems (50)(51)(52) and their potential relevance in the sulfur, nitrogen, and carbon cycles (33,(53)(54)(55). However, their specific ecological interactions within the microbial communities remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%